2019
DOI: 10.1039/c8na00291f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of stable and phase-adjustable CsPbBr3@Cs4PbBr6 nanocrystals via novel anion–cation reactions

Abstract: In this study, a novel anion–cation method to synthesize highly emissive and stable diphase CsPbBr3@Cs4PbBr6 composite NCs has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 49 publications
8
55
0
1
Order By: Relevance
“…In traditional dual-source vacuum deposition process, the CsBr and PbBr 2 precursors are deposited on the substrate by controlling the thickness followed by the annealing process to form CsPbBr 3 film (Fig. 12a) Further, Hua et al [126] reported the pressure assisted multi-step sequential dual-source vacuum deposition (MS-DSVD) method to prepare compact CsPbBr 3 perovskite films ( poly-triarylamine (PTAA) [78,95] or NiO x [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] are the commonly used as HTLs.…”
Section: Sequential Evaporation Methodsmentioning
confidence: 99%
“…In traditional dual-source vacuum deposition process, the CsBr and PbBr 2 precursors are deposited on the substrate by controlling the thickness followed by the annealing process to form CsPbBr 3 film (Fig. 12a) Further, Hua et al [126] reported the pressure assisted multi-step sequential dual-source vacuum deposition (MS-DSVD) method to prepare compact CsPbBr 3 perovskite films ( poly-triarylamine (PTAA) [78,95] or NiO x [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] are the commonly used as HTLs.…”
Section: Sequential Evaporation Methodsmentioning
confidence: 99%
“…In addition to the enhanced optical properties, the durability of CsPbBr 3 NCs was significantly improved by the introduction of Cs 4 PbBr 6 , one such feature being their thermal stability. [189][190][191][192] In a heating and cooling cycle, the PL intensity of pristine CsPbBr 3 and CsPbBr 3 /Cs 4 PbBr 6 composite was quenched as the temperature increased. During the cooling procedure, the quenching was gradually recovered, but never recovers to the original state.…”
Section: Nanosized Compositementioning
confidence: 99%
“…[9,34] A quite different approach involves CsPbBr 3 NCs being embedded in a Cs 4 PbBr 6 matrix with a crystal size of several hundred nanometers or more, resulting in improved PLQY and stability. [35][36][37][38] However, the literature reports in this area have been focused only on green emission, and Cs 4 PbBr 6 /CsPbBr 3 embedded structures are not suitable for electroluminescent devices because a 0D Cs 4 PbBr 6 phase has a wide bandgap of 3.95 eV and is insulating. [39,40] In this article, we report a unique method to enhance the PLQY and stability of blue-emitting CsPbBr 3 QDs via simultaneous generation of mixed CsPbBr 3 QDs and Cs 4 PbBr 6 NCs.…”
Section: Introductionmentioning
confidence: 99%